Journey to Pleasant Prarie: Mattie's Pledge - Book 2 Book 2 - Drexler, Jan (Grand Rapids, MI : Revell, a division of Baker Publishing Group, 2016)
Mattie Schrock is no stranger to uprooting her life. Even as her father relocated her family from one Amish community to the next, she always managed to find a footing in their new homes. Now as the Schrock family plans to move west from Somerset County to a fledgling Amish settlement in Indiana, she looks forward to connecting with old friends who will be joining them from another Pennsylvania community--friends like Jacob Yoder, who has always held a special place in her heart. Since Mattie last saw Jacob, theyve both grown into different people with different dreams. Jacob yearns to settle down, but Mattie cant help but dream of what may lie over the western horizon. When a handsome Englisher tempts her to leave the Amish behind to search for adventure in the West, will her pledge to Jacob be the anchor that holds her secure? Tender, poignant, and gentle, Matties Pledge offers readers a glimpse into Amish life in the 1840s--and into the yearning heart of a character theyll not soon forget.
Keywords: Amish -- Fiction; Woman-man relationships; Christian fiction; Love stories